Perceptual Tolerance to Motion-To-Photon Latency with Head Movement in Virtual Reality - Yang, Minxia; Zhang, Jiaqi; Yu, Lu (Picture Coding Symposium, 2019)
Since Motion-To-Photon (MTP) latency is inevitable and can be perceived in virtual reality, quantifying perception of MTP latency becomes necessary. In this paper, we investigate perceptual tolerance to MTP latency, including perception threshold of the latency and user acceptance of delays above the threshold. It is affected by different head motion events, such as Motion-Static-Alternate (MSA, i.e., an acceleration or deceleration in one direction) and Motion-To-Reverse (MTR, i.e., a movement reverses direction). In each motion event, rotation angle and angular velocity also influence perception of MTP latency. Experimental results show that subjects are more intolerant of MTP latency in MTR than MSA. The latency perception threshold is about 23 ms when subjects turn their heads at the maximum speed of human limits. When the angular velocity decreases, the perception threshold increases. The maximum threshold is ~41 ms at 20 °/s in this study. Inversely proportional models are established to describe the relationship between threshold and angular velocity. Besides, MTP latency over the threshold is harder to be accepted with the rotation angle decreasing or the angular velocity increasing.